Esophageal Foreign Body Causing Direct Aortic Injury - ECS Lam; JA Brown; JS Whittaker (Canadian Journal of Gastroenterology)
Foreign bodies in the esophagus are uncommon causes of esophageal perforation. Many nonperforating cases are successfully managed by flexible gastroscopy. However, complicated foreign bodies such as those that result in esophageal perforation and vascular injury are best managed surgically. Gastroscopy remains the primary method of diagnosis. A case of a 59-year-old woman who developed retrosternal and intrascapular pain, odynophagia and hematemesis after eating fish is reported. Flexible gastroscopy showed arterial bleeding from the midthoracic esophagus. Computed tomography scan localized a 3 cm fish bone perforating the esophagus with surrounding hematoma. An aortogram did not reveal an actively bleeding aortoesophageal fistula. The fish bone was surgically removed and the patient recovered with no postoperative complications. This case illustrates the importance of early consideration for surgical intervention when confronted with a brisk arterial bleed from the esophagus with suggestive history of foreign body ingestion.